Lábrea - Alessandra de Souza Fonseca; Victor Fernandes Queiroz; Antônio Fladsoney Pereira da Silva; João Henrique Lopes da Silva; Mizael Nascimento Rodrigues; Newton Coelho Monteiro (Lifestyle Journal, 2022)
Lábrea, Amazonas, Brazil officially has 64.4% of its public streets lined with trees. However, there is no information available on the qualitative and quantitative aspects of this afforestation. The aim of the study was to inventory the urban afforestation of Lábrea to quantify and qualify the municipal road afforestation. The census of arboreal vegetation on the public roads covered parking lots and areas for pedestrian traffic (sidewalks and curbs) on the streets of the neighborhoods that make up the urban area, being recorded geolocated images of individuals. A total of 507 individuals were counted, distributed in 38 species and 15 botanical families, planting trees in the city’s public streets. The species ficus (Moraceae, Ficus benjamina) and jambeiro (Myrtaceae, Syzygium malaccense) had the highest absolute density. Afforestation is concentrated in the Centro district (50%). Disregarding the neighborhood, the most tree-lined street was October 22nd. The species are partially of native national origin (19 species, 50%), of which 63% are Amazonian (12 species). In absolute terms, individuals are mostly of exotic origin (79%). The individuals are in good structural condition, with type 1 phytosanitary status, located in sidewalks, conflicting or not with the electrical network (413 ind., 81%) without conflicts with the pavement (402 ind., 79%), outside the phenological period. Some common problems already reported also occur in the region. The low diversity of species in afforestation may indicate a certain loss in the quality of the urban physical and environmental structure.